Molecular and electronic properties of HIV-1 protease inhibitor C60derivatives as studied by the ONIOM method - Siriporn Promsri (2018)
Quantum chemical methods were performed to study the structure and electronic properties of a series of C60derivatives. The integrated, ONIOM molecular orbital method was applied to optimize the structure of all compounds while the DFT/B3LYP 6-31G(d) calculations were performed to examine molecular and electronic properties. It was found that strongest effect of the functional groups on the net charges takes place on the linked atoms between C60and its side chain. The functional group leads to the changes of atomic net charges on the C60surface up to 5 Å away from the C-C bond where the functional group binds to the surface. Two localized electrostatic potential regions are observed, for the selected compounds, near the hydroxyl oxygen and the hydroxyl hydrogen. The hydroxyl hydrogen atom is the location of the most positive potential. These electrostatic features are likely modulated the hydrophobicity or lipophilicity of the compounds and, hence, indicate how they interact with the receptor. © 2004 Elsevier B.V. All rights reserved.